Diagnosing NAFLD in Diabetic Patients with circRNA CDR1as: An Analysis of Efficacy and Correlation with Glucose Metabolism: CircRNA CDR1as: NAFLD Diagnostic Biomarker in Diabetes - Zhang, Jingjing; Zhang, Xinzhi; Apaer, Shadike; Zhang, Shuo; Liang, Guangyou; Dong, Qiang; Huang, Jinchuang; Li, Tao; Cao, Xinling (Journal of Medical Biochemistry, 2025)
Objective: To explore the expression characteristics and diagnostic efficacy of circRNA CDR1as, as well as its correlation with glucose metabolism disorders in patients with diabetes mellitus (DM) complicated by non-alcoholic fatty liver disease (NAFLD), so as to provide a novel target for precision diagnosis and treatment. Methods: From May 2024 to August 2025, 74 DM patients complicated by NAFLD (research group) and 71 patients with uncomplicated DM (control group) were included. Serum CDR1as levels were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR), fasting insulin (FINS) by chemiluminescence, fasting blood glucose (FPG) by a blood glucose meter, and glycosylated hemoglobin (HbA1c) by high-performance liquid chromatography (HPLC). The homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. The diagnostic efficacy of CDR1as was evaluated by receiver operating characteristic (ROC) curves, and the correlation between CDR1as and glucose metabolism indexes was analyzed. Results: CDR1as was expressed at an elevated level (29.00% greater) in the research group than in controls (P<0.05). In diagnosing NAFLD in DM cases, CDR1as showed an area under the ROC curve (AUC) of 0.781 (sensitivity 64.86%, specificity 80.28%). In stratified analysis, CDR1as exhibited superiority in diagnosing moderate and severe steatosis (S2/S3), with AUCs of 0.829 and 0.878, respectively. HOMA-IR, FINS, FPG, and HbA1c, all of which were higher in the research group compared to controls (P<0.05), showed a positive correlation with CDR1as. Treatment induced a decline in CDR1as expression (P<0.05), with higher levels observed in patients with a poor prognosis versus those with favorable outcomes (P<0.05). According to ROC curve analysis, the AUC of CDR1as in predicting prognosis was 0.747, with 57.14% sensitivity and 84.78% specificity. Conclusion: CDR1as is over-expressed in DM patients with NAFLD, which can serve as a novel biomarker to diagnose NAFLD and evaluate glucose metabolism disorders.